2008
DOI: 10.1103/physrevlett.100.046102
|View full text |Cite
|
Sign up to set email alerts
|

Torque and Twist against Superlubricity

Abstract: Superlubricity between incommensurate surfaces provides a desired low-friction state essential for the function of small-scale machines. Here we demonstrate experimentally and theoretically that superlubricity in contacts lubricated by lamellar solids might be eliminated due to torque-induced reorientation coupled to lateral motion. We find that the possibility of reorientation always leads to stabilization of a high frictional state which corresponds to a commensurate configuration. DOI: 10.1103/PhysRevLett.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
212
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(227 citation statements)
references
References 29 publications
15
212
0
Order By: Relevance
“…Specifically at the nanoscale, peculiar means to control friction would be available, for instance the commensurability of the crystal lattices of the sliding nano-objects and the onset of a superlubric state [25]. However, once the materials have been chosen, it is hard to modify the contact geometry and no efficient friction control can be achieved [12,13]. One possibility to circumvent this difficulty is to tune the material properties through some external parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically at the nanoscale, peculiar means to control friction would be available, for instance the commensurability of the crystal lattices of the sliding nano-objects and the onset of a superlubric state [25]. However, once the materials have been chosen, it is hard to modify the contact geometry and no efficient friction control can be achieved [12,13]. One possibility to circumvent this difficulty is to tune the material properties through some external parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, at incommensurate interfaces, atomic friction studies revealed a superlubrication regime, where the friction coefficient vanishes 15,16 . This behaviour can be explained by simple mechanical models such as the FrenkelKontorova model, a generalized Prandtl-Tomlinson scheme or the double-chain model [17][18][19][20] . In the Frenkel-Kontorova approach the interface between two solids is described by a monolayer of elastically interacting beads on a periodic substrate potential [5][6][7][8] .…”
mentioning
confidence: 99%
“…Superlubricity is experimentally rare. Until recently, it has been demonstrated or implied in a relatively small number of cases [29,[42][43][44][45][46]. There are now more evidences of superlubric behavior in cluster nanomanipulation [32,33,47], sliding colloidal layers [48][49][50], and inertially driven rare-gas adsorbates [51,52] (see Fig.…”
Section: Contact Area Dependence and New Perspectives In Superlubricitymentioning
confidence: 99%